Peer Feedback Technique on Students’ Writing Narrative Text Ability - Rayendriani Fahmei Lubis (English Education : English Journal for Teaching and Learning, 2021)
This research is intended to investigate the effect of Peer Feedback Technique on Students’ Writing Narrative Text Ability at XI Grade MAN Tapanuli Selatan. This research used experimental quantitative method with pre-test and post-test design. The populations were all of the students at XI Grade MAN Tapanuli Selatan. The sample were XI MIA 1 as experimental class that consisted of 20 students and XI MIA 2 as control class that consisted of 20 students. The data were collected through pre-test and post-test in essay test form and analyzed by using Statistical Package for Social Sciences (SPSS) with T-test. After doing T-test, the finding showed that the t-test value was sig (2- tailed) 0.05 (0.017 0.05. Therefore, alternative hypothesis (Ha) of this research was accepted null hypothesis (H0) was rejected. It can be concluded that there was significant effect of using peer feedback technique on students’ writing narrative text ability at XI grade MAN Tapanuli Selatan